Protracted conflict in Myanmar and role of international actors - Md Mahbubul Haque, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Myanmar, one of Southeast Asia's most ethnically diverse nations, continues to grapple with profound challenges in nation-building despite achieving independence 76 years ago. Protracted tensions between the military and ethnic minorities have significantly hindered progress. On 1 February 2021, the military staged a coup, detaining key political figures, including State Counsellor Aung San Suu Kyi. The aftermath has been devastating, with nearly 6,000 fatalities, over 3.3 million people displaced, and more than half the population now living below the poverty line, predominantly due to violence perpetrated by the military. This study examines the ongoing conflict in Myanmar through the lens of international relations, focusing on the role of international actors in addressing the crisis. Employing a qualitative approach, the research analyses secondary data, including reports, policy documents, and scholarly articles, to explore the geopolitical implications of Myanmar’s unrest. The findings highlight the strategic importance of Myanmar’s location, which shapes its interactions with neighbouring countries and global powers. The protracted conflict has exacerbated domestic instability and generated security concerns for bordering nations, threatening regional peace and stability. This research underscores the critical role of international actors in mediating the crisis and fostering long-term solutions. It calls for a coordinated global response to address the humanitarian crisis, mitigate regional risks, and promote sustainable peace in Myanmar.